Impact of Climate Change on Agricultural Productivity in Asia - Okamoto, Katsuo (Annals of Arid Zone, 2016)
Will Asian people have sufficient food in the 21" century? In this paper, predicting long-term (the time scale of 50 to 100 years) crop yield of major crops (rice, wheat and maize) were focused on. First, a general view of changes in the area and distribution of agricultural land in the past and climate change in the future was provided. Second, results of studies on change in the area for cultivating crops and yield in accordance with climate change were presented. The sizes of suitable and potential regions for cultivating major crops will remain in the status quo or expand. The yield per unit area will increase in accordance with the increase in climatology-based potential productivity. Climate change is not an event on the scale of a few years but on the scale of 50 to 100 years. Therefore, we have sufficient time todevelopanew variety suitable for changedenvironments. Consequently, even if the global climate will change, the amount of food produced will meet the demands in Asia.